The influence of usefulness, entertainment, interaction, enjoyment, and familiarity to purchase music platform subscriptions in Millennials and Gen-z communities through trust mediation - Golan Hasan; Ervi Scorpianti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
Advances in technology significantly transform the means of communication between users and companies. The music industry is also experiencing technological innovation as more consumers subscribe to paid and free online streaming services. Therefore, this study aimed to determine the effect of usefulness, entertainment, interaction, enjoyment, and familiarity on purchase intention for music streaming platform subscriptions in millennials and gen-z communities in Batam City through trust mediation. A quantitative method was adopted with data collected through questionnaires from 348 respondents and processed using the Partial Least Square program. The results indicated that familiarity and interaction significantly influenced purchase intention through trust mediation. As managerial implications, familiarity must be increased for trust and interaction to influence purchase intention. This study only focused on millennials and gen-z communities and conducted a survey through Google Forms. Therefore, future studies could expand the scope beyond a single generation or region.